COFFEE INTAKE AND ELEVATED LIPID PROFILE IN AMI PATIENTS - Rehman, Muhammad Abdul; Haq, Hafiz Hafeez-ul-; Tayyab, Muhammad; Khan, Faiz Ahmed (Journal of Ayub Medical College Abbottabad, 1996)
Coffee intake from diet records was studied in association with serum lipid profile concentrations in a crosssectional sample of 60 middle aged men and women suffering from acute myocardial infarction to determine the significance and form of their interrelationships. All the subjects were evaluated for diabetes mellitus, nephrotic syndrome and hyper lipid - anemia. Heavy drinking of coffee revealed a highly significant (p <0.001) increase in levels of total cholesterol and LDL-cholesterol. Graphic analysis revealed that serum concentrations of total cholesterol and LDLcholesterol were positively related, which were statistically less significant (p<0.01) to intake of upto 3 cups of coffee per day and more significant (p<0.001) with intake exceeding 3-4 cups. These results suggest that heavy coffee drinking patients of acute myocardial infarction have significant increases in levels of lipoprotein profiles when compared to those faking no coffee.